2019
DOI: 10.1016/j.jstrokecerebrovasdis.2018.12.006
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Impact of Thrombophilia Screening in Young Adults with Ischemic Stroke

Abstract: Objective: We evaluated the ability of genetic and serological testing to diagnose clinically relevant thrombophilias in young adults with ischemic stroke. Methods: We performed a retrospective cohort study of patients aged 18-65 years diagnosed with acute ischemic stroke at a comprehensive stroke center between 2011-2015 with laboratory testing for thrombophilia. The primary outcome was any positive thrombophilia screening test. The secondary outcome was a change in clinical management based on thrombophilia … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

2
28
0
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 32 publications
(33 citation statements)
references
References 32 publications
(25 reference statements)
2
28
0
3
Order By: Relevance
“…Although there is uncertainty about the utility of performing thrombophilia screening in stroke patients, such testing remains common in clinical practice, especially in young people. Consistent with the results of previous case-control studies and meta-analysis, 27-30 but conversely with those of more recently published studies, 10,31 in our series of stroke patients the common thrombophilic gene polymorphisms FV Leiden, PTH G20210A, MTHFR C677T, the physiological inhibitors of clotting factors (PC, PS, ATIII), and the acquired LAC were not related to the occurrence of IS. This finding supports the concept that in daily clinical practice, the search for inherited prothrombotic factors in patients with IS is rarely indicated.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…Although there is uncertainty about the utility of performing thrombophilia screening in stroke patients, such testing remains common in clinical practice, especially in young people. Consistent with the results of previous case-control studies and meta-analysis, 27-30 but conversely with those of more recently published studies, 10,31 in our series of stroke patients the common thrombophilic gene polymorphisms FV Leiden, PTH G20210A, MTHFR C677T, the physiological inhibitors of clotting factors (PC, PS, ATIII), and the acquired LAC were not related to the occurrence of IS. This finding supports the concept that in daily clinical practice, the search for inherited prothrombotic factors in patients with IS is rarely indicated.…”
Section: Discussionsupporting
confidence: 93%
“…These findings confirmed that hyperhomocysteinemia may be a transient consequence of the thrombotic event. 32 However, they seem to be in conflict with data from other reports, 28, 31, 33 in particular with the results of a Chinese study that showed no differences in serum homocysteine levels immediately after a stroke and after 3 months. 34 However, the stroke population examined by these authors was not homogeneous and included both IS and transient ischemic attacks.…”
Section: Discussionmentioning
confidence: 57%
See 1 more Smart Citation
“…Sin embargo, a pesar de haberse encontrado una asociación significativa entre múltiples trombofilias hereditarias e ictus isquémico, ello no puede ser tomado como evidencia de una relación causal ni tampoco apoyar al testeo de trombofilia en la práctica clínica (13,14) . De esta manera, se necesitan más estudios para determinar si el estudio de una trombofilia en casos de ictus isquémicos o AIT es beneficioso.…”
Section: Discussionunclassified
“…Nevertheless, this laboratory diagnosis led to a change in patient management in approximately one-third of the cases. 87 According to the second concept of study design, in which AT-, PC-or PS-deficient cohorts are investigated for ATE, the majority of published reports focus on AT deficiency. In this field, large cohort studies of 5 study groups are available.…”
mentioning
confidence: 99%